Stress among university students: a case study of UiTM Johor / Fatin Farazh Ya’acob ... [et al.] - Ya’acob, Fatin Farazh; Badyalina, Basri; Zainoddin, Amir Imran; Abd Jalal, Muhammad Zulqarnain Hakim; Zamani, Nur Diana; Mohamad Khalid, Rusnani (Universiti Teknologi MARA, Perlis, 2025)
This study investigates the relationships between interpersonal, intrapersonal, and academic stressors and their impact on overall stress levels among students at UiTM Segamat. The primary objective is to identify key stress factors influencing mental well-being and provide insights for effective interventions. Data were collected from 340 respondents using a structured questionnaire distributed online, with simple random sampling ensuring a representative sample. The reliability of the questionnaire was assessed using Cronbach's alpha, which demonstrated good internal consistency for most constructs. Multiple linear regression analysis was employed to examine the predictive relationships between stressors and overall stress levels. The findings revealed that all three stressor categories significantly contributed to students' stress levels, with academic stressors exerting the strongest influence. The model explained 74.6% of the variance in stress levels, underscoring the complexity of factors affecting student well-being. These results emphasize the need for targeted interventions focusing on academic pressures, interpersonal relationships, and internal psychological challenges. By addressing these stressors, educational institutions can better support students’ mental health and academic performance, fostering a healthier and more conducive learning environment.